Clinical Characteristics and Outcomes of Multiple Sclerosis and Neuromyelitis Optica Spectrum Disorder With Brainstem Lesions as Heralding Prodrome - Ji, Qiling; Dong, Huiqing; Lee, Hangil; Liu, Zheng; Tong, Yanna; Elkin, Kenneth; Haddad, Yazeed; Geng, Xiaokun; Ding, Yuchuan (Frontiers in Neurology, 2022)
Objective The present study sought to differentiate multiple sclerosis and neuromyelitis optica spectrum disorder patients at their first attack by describing and distinguishing their clinical features, radiographic characteristics, and immunologic characteristics of serum and cerebrospinal fluid. Methods We retrospectively studied 58 patients with multiple sclerosis (MS) and 52 patients with neuromyelitis optica spectrum disorder (NMOSD) by referencing brainstem lesions as the prodromal events. Their demographics and presentation at the time of the first attack was evaluated including their gender, age, clinical features of the first attack, the expanded disability status scale (EDSS), brainstem lesion(s) by head MRI, and immunological indices of serum and cerebrospinal fluid. Results The NMOSD group had more female patients (4.8 vs. 1.9, p < 0.05), and was older than the MS group (37.81 ± 16.60 vs. 27.57 ± 11.17, p <0.001). NMOSD patients also had a significantly higher association with autoimmune diseases or positive autoimmune antibodies (p < 0.01). There was no significant difference in the EDSS scores between the two groups (p = 0.420). Central hiccups, vomiting, and pyramidal tract signs were more common in the NMOSD group than the MS group (p < 0.001, p < 0.001, p < 0.01), while eye movement abnormalities were more common with MS (p < 0.01). There were no significant differences in other clinical manifestations such as vertigo, diplopia, limb weakness, numbness, and eating difficulty. MS patients were more likely to have midbrain and pons imaging lesions (p < 0.001, p < 0.001), while NMOSD patients had more lesions in the medulla oblongata (p < 0.001). The lesions in the MS group were mostly located in the periphery, while those in the NMOSD group were centrally located (p < 0.001, p < 0.001). Patchy lesions were more common in MS patients (p < 0.001), while large lesions were more common in the NMOSD group (p < 0.001). Finally, serum AQP4 Ab was found only in the NMOSD group (p < 0.001). Conclusion Patients with MS and NMOSD have differentiating clinical manifestations at the time of their first brainstem lesions which include central hiccups, vomiting, pyramidal tract signs, and abnormal eye movements. Additionally, distinct imaging manifestations such as lesion location(s) and morphology may also aid in the development of pathognomonic criteria leading to timely initial diagnosis of MS and NMOSD.